2017
DOI: 10.7554/elife.29222
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic eye tracking in mice

Abstract: Eye movements provide insights about a wide range of brain functions, from sensorimotor integration to cognition; hence, the measurement of eye movements is an important tool in neuroscience research. We describe a method, based on magnetic sensing, for measuring eye movements in head-fixed and freely moving mice. A small magnet was surgically implanted on the eye, and changes in the magnet angle as the eye rotated were detected by a magnetic field sensor. Systematic testing demonstrated high resolution measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 95 publications
(168 reference statements)
10
82
1
Order By: Relevance
“…Figure 2C shows example traces of the horizontal position of the two eyes (top), along with running speed of the mouse (bottom). As described previously [5][6][7] and analyzed below ( Figure 3D), the eyes are generally stable when the mouse is not moving. In addition, the raw traces reveal a pattern of eye movement wherein rapid correlated movements of the two eyes are superimposed on slower anti-correlated movements.…”
Section: Figure 1 Tracking Eye and Head Movements During Prey Capturesupporting
confidence: 69%
See 3 more Smart Citations
“…Figure 2C shows example traces of the horizontal position of the two eyes (top), along with running speed of the mouse (bottom). As described previously [5][6][7] and analyzed below ( Figure 3D), the eyes are generally stable when the mouse is not moving. In addition, the raw traces reveal a pattern of eye movement wherein rapid correlated movements of the two eyes are superimposed on slower anti-correlated movements.…”
Section: Figure 1 Tracking Eye and Head Movements During Prey Capturesupporting
confidence: 69%
“…Many studies have reported a limited range of infrequent eye movements in head restrained mice [6,25,28,29] , consistent with the idea that eye movements are generally driven by head movement.…”
Section: Coordinated Horizontal Eye Movements Are Primarily Compensatsupporting
confidence: 54%
See 2 more Smart Citations
“…Although these systems are fast and reliable, their spatial resolution is heavily limited by the number of sensors deployed. Despite the availability of various other sensors, including microwave based motion detectors [29] , ultrasonic microphones [30,31] , radiofrequency detectors [32] , global positioning systems [33] , and heat (infrared) sensors [34] , majority of existing tracking systems rely on video cameras, as they provide detailed images of whole bodies [4,[35][36][37][38] , [39] , individual limbs [40][41][42] , face and whisker motion [43] , and eye movements [44,45] . A major drawback, however, is that behavioral classification requires several image processing steps to detect and identify the object of interest which takes several tens of milliseconds using the current state-of-art algorithms and standard computing infrastructure.…”
Section: Introductionmentioning
confidence: 99%